Early deterioration, hematoma expansion, and outcomes in deep versus lobar intracerebral hemorrhage: the FAST trial - Kuohn, Lindsey R.; Witsch, Jens; Steiner, Thorsten; Sheth, Kevin N.; Kamel, Hooman; Navi, Babak B.; Merkler, Alexander E.; Murthy, Santosh B.; Mayer, Stephan A. (Stroke, 2022)
Background: - - In patients with intracerebral hemorrhage (ICH), it is unclear whether early neurological deterioration, hematoma expansion (HE), and outcome vary by supratentorial ICH location (deep versus lobar). Herein, we assessed these relationships in a clinical trial cohort that underwent brain imaging early after symptom onset. We hypothesized that HE would occur more frequently, and outcome would be worse in patients with deep ICH. - - Methods: - - We performed a post hoc analysis of the FAST (Factor-VII-for-Acute-Hemorrhagic-Stroke-Treatment) trial including all patients with supratentorial hemorrhage. Enrolled patients underwent brain imaging within 3 hours of symptom onset and 24 hours after randomization. Multivariable regression was used to test the association between ICH location and 3 outcomes: HE (increase of ≥33% or 6mL), early neurological deterioration (decrease in Glasgow Coma Scale score ≥2 points or increase in National Institutes of Health Stroke Scale ≥4 points within 24 hours of admission), and 90-day outcome (modified Rankin Scale). - - Results: - - Of 841 FAST trial patients, we included 728 (mean age 64 years, 38% women) with supratentorial hemorrhages (deep n=623, lobar n=105). HE (44 versus 27%, P=0.001) and early neurological deterioration (31 versus 17%, P=0.001) were more common in lobar hemorrhages. Deep hemorrhages were smaller than lobar hemorrhages at baseline (12 versus 35mL, P<0.001) and 24 hours (14 versus 38mL, P<0.001). Unadjusted 90-day outcome was worse in lobar compared with deep ICH (median modified Rankin Scale score 5 versus 4, P=0.03). However, when adjusting for variables included in the ICH score including ICH volume, deep location was associated with worse and lobar location with better outcome (odds ratio lobar location, 0.58 [95% CI, 0.38-0.89]; P=0.01). - - Conclusions: - - In this secondary analysis of randomized trial patients, lobar ICH location was associated with larger ICH volume, more HE and early neurological deterioration, and worse outcome than deep ICH. After adjustment for prognostic variables, however, deep ICH was associated with worse outcome, likely due to their proximity to eloquent brain structures.